A perovskite crystal detection reagent and its preparation method and detection method

By using perovskite crystal detection reagents containing active substances and antisolvents, the accuracy and efficiency of perovskite crystal quality judgment in the prior art are solved, and a rapid and accurate crystal quality evaluation is achieved, reducing costs.

CN115219487BActive Publication Date: 2025-04-15HUBEI WONDER SOLAR LLC
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202210840971.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-07-18
Publication Date
2025-04-15
Estimated Expiration
2042-07-18

AI Technical Summary

Technical Problem

In the prior art, the method of judging perovskite crystal quality is not accurate, complex in operation, low testing efficiency, and requires the use of more expensive instruments.

Method used

A perovskite crystal detection reagent is provided, including active substances and anti-solvents, which enter the perovskite layer through free diffusion. After the anti-solvent evaporates, the active substance reacts with the perovskite crystals, resulting in different degrees of decomposition, and the crystallization mass is judged by color changes.

Benefits of technology

It realizes simple, fast and accurate judgment of the quality of perovskite crystals, reduces the cost of materials, instruments and time, and avoids the need to use valuable instruments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115219487B_ABST
    Figure CN115219487B_ABST
Patent Text Reader

Abstract

The present invention provides a perovskite crystallization detection reagent and a preparation method and a detection method thereof. The perovskite crystallization detection reagent of the present invention comprises: an active substance and an anti-solvent; the active substance is one or more of a polar inorganic substance, an organic acid, an organic base, and a weak oxidant; the anti-solvent is one or more of isopropanol, chlorobenzene, toluene, chloroform, acetonitrile, and ethyl acetate. The perovskite crystallization detection reagent of the present invention can greatly improve the analysis efficiency, greatly reduce the cost of materials, instruments, and time, and can simply, quickly, and accurately judge the quality of perovskite crystallization.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of perovskite solar cells, and in particular to a perovskite crystallization detection reagent and a preparation method and a detection method thereof. Background Art

[0002] In recent years, "perovskite solar cells" based on ABX3 crystal structure perovskite materials have attracted much attention. Due to the excellent photoelectric properties of perovskite, such as long carrier diffusion length, adjustable optical band gap, high molar extinction coefficient and bipolar transmission, its cell conversion efficiency has increased from 3.8% to the current 25.7% in just a few years. At the same time, perovskite cell devices have the characteristics of being able to be prepared by the full solution method, simple manufacturing process, wide source of raw materials and high photoelectric conversion efficiency, which creates conditions for large-scale production.

[0003] The quality of perovskite crystallization in metal halide perovskite solar cells (PSCs) has a decisive influence on its photoelectric conversion efficiency (PCE). In order to understand the crystallization status of perovskite, the current methods for judging the quality of perovskite crystallization mainly include naked eye observation, photovoltaic characteristic (JV) test method, X-ray diffraction (XRD) test method and scanning electron microscope observation (SEM).

[0004] Among them, the naked eye observation method cannot distinguish and judge microscopic grain boundaries and grains with low crystallinity; the JV test method can only indirectly reflect the crystallization status, and may require repeated tests; the XRD test method requires the use of more expensive instruments, which is not simple enough and difficult to distinguish the crystallization differences in different local areas; the SEM test method also requires the use of expensive instruments, the sample preparation and testing process is complicated, and can only observe the crystallization status of micron and nanometer scale areas. In addition, for perovskite crystals grown in a mesoporous skeleton, the resolution of the SEM test method is greatly affected by the skeleton nanoparticles.

[0005] In view of this, there is an urgent need to propose a method for detecting perovskite crystallization that can simply, quickly and accurately determine the quality of perovskite crystallization. Summary of the invention

[0006] The technical problem to be solved by the present invention is to provide a perovskite crystallization detection reagent and a preparation method and a detection method thereof, so as to solve the problems in the prior art that the method for judging the quality of perovskite crystallization is not accurate, the operation is complicated, the test efficiency is low, and expensive instruments are required.

[0007] In order to solve the above technical problems, the technical solution of the present invention is as follows:

[0008] A perovskite crystallization detection reagent, comprising: an active substance and an antisolvent;

[0009] The active substance is one or more of polar inorganic substances, organic acids, organic bases, and weak oxidants;

[0010] The anti-solvent is one or more of isopropanol, chlorobenzene, toluene, chloroform, acetonitrile and ethyl acetate.

[0011] Preferably, the polar inorganic substance is one or more of water, hydrogen sulfide, ammonia, hydrogen chloride, hydrogen bromide, and phosphoric acid;

[0012] The organic acid is one or more of formic acid, acetic acid, benzenesulfonic acid, and trifluoromethanesulfonic acid;

[0013] The organic base is one or more of pyridine, 4-tert-butylpyridine, furan, methylamine, formamide, and acetamide;

[0014] The weak oxidant is one or more of hydrogen peroxide, elemental iodine, and elemental sulfur.

[0015] Preferably, the molar concentration of the active substance is less than or equal to 0.1 mol / L;

[0016] Optionally, the volume fraction of the active substance is less than or equal to 10%.

[0017] Preferably, the perovskite crystallization detection reagent is prepared by mixing water and isopropanol in a volume ratio of 1:9; or,

[0018] The perovskite crystal detection reagent is prepared by mixing 4-tert-butylpyridine and isopropanol, and the molar concentration of the 4-tert-butylpyridine is 0.05 mol / L; or,

[0019] The perovskite crystallization detection reagent is prepared by mixing hydrogen peroxide and isopropyl alcohol in a volume ratio of 1:9.

[0020] The present invention also provides a method for preparing the perovskite crystal detection reagent, comprising the following steps: dissolving the active substance in an anti-solvent to obtain.

[0021] The present invention also provides a perovskite crystal detection method, comprising the following steps:

[0022] Taking a material to be tested, distributing the perovskite crystallization detection reagent on the surface of the material to be tested, and volatilizing the volatile components of the perovskite crystallization detection reagent, determining the morphology of the material to be tested, and obtaining a detection conclusion;

[0023] Wherein, the material to be tested is an electrode of a solar cell having a perovskite crystal structure.

[0024] Preferably, the perovskite crystallization detection reagent is distributed on the surface of the material to be tested by dripping; or, the perovskite crystallization detection reagent is distributed on the surface of the material to be tested by immersion; or, the perovskite crystallization detection reagent is distributed on the surface of the material to be tested by coating.

[0025] Preferably, the detection conclusion is obtained according to the morphology of the material to be tested:

[0026] The color of the material to be tested includes black, brown, gray, yellow, red, and white; if the grayscale of the color of the material to be tested is high, the perovskite crystal quality is high; if the grayscale of the color of the material to be tested is low, the perovskite crystal quality is low. The grayscale can be quantitatively detected by the grayscale value, and the grayscale value ranges from 0 to 255, with white being 255 and black being 0.

[0027] Preferably, if the area of ​​the region with high grayscale color of the material to be tested is large, the perovskite crystal quality is high; if the area of ​​the region with low grayscale color of the material to be tested is large, the perovskite crystal quality is low.

[0028] Preferably, the solar cell is one of a printable mesoscopic perovskite solar cell, a formal mesoporous structure perovskite solar cell, a formal planar structure perovskite solar cell, an inverted mesoporous structure perovskite solar cell, and an inverted planar structure perovskite solar cell.

[0029] The above solution of the present invention includes at least the following beneficial effects:

[0030] (1) The perovskite crystallization detection reagent of the present invention comprises: an active substance and an anti-solvent. The perovskite crystallization detection reagent enters the perovskite layer by free diffusion, the anti-solvent does not react with the perovskite crystal and is easily volatilized, and after the anti-solvent is completely volatilized, the active substance fully contacts and reacts with the perovskite crystal, causing the perovskite to decompose to varying degrees. For areas with poor crystallization quality, this decomposition process is more significant, while areas with good crystallization quality are basically unaffected, and the different changes of the perovskite are reflected in the changes in its color.

[0031] (2) The perovskite crystallization detection method of the present invention uses a detection reagent to "deliberately" destroy and reconstruct the perovskite to a certain extent during crystallization analysis, and obtains information on the quality of perovskite crystallization in different regions after the volatile substances evaporate for about tens of seconds, thereby improving analysis efficiency, greatly reducing material, instrument and time costs, and being able to simply, quickly and accurately judge the quality of perovskite crystallization. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 is a front view of the material to be tested before testing in Example 1 of the present invention;

[0033] Figure 2 is a back view of the material to be tested before testing in Example 1 of the present invention;

[0034] Figure 3 is a front view of the material to be tested after testing according to Example 1 of the present invention;

[0035] Figure 4 It is a back view of the material to be tested after testing in Example 1 of the present invention. DETAILED DESCRIPTION

[0036] In the embodiments of the present invention, if the specific conditions are not specified, the conventional conditions or the conditions recommended by the manufacturer are followed. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially. Raw materials of different manufacturers and models do not affect the implementation of the technical solution of the present invention and the realization of the technical effects.

[0037] Example 1

[0038] The perovskite crystallization detection reagent of this embodiment includes: an active substance and an anti-solvent;

[0039] Wherein, the active substance is water; the anti-solvent is isopropanol. The perovskite crystallization detection reagent is formed by mixing water and isopropanol in a volume ratio of 1:9. The perovskite crystallization detection method of this embodiment includes the following steps:

[0040] Taking a material to be tested, distributing the perovskite crystallization detection reagent on the surface of the material to be tested, and volatilizing the volatile components of the perovskite crystallization detection reagent, determining the morphology of the material to be tested, and obtaining a detection conclusion;

[0041] Wherein, the material to be tested is an electrode of a solar cell having a perovskite crystal structure. In this embodiment, the solar cell is a printable mesoscopic MAPbI3 perovskite solar cell. Wherein, the MAPbI3 refers to CH3NH3PbI3.

[0042] The active substance is water, and the reactions that can occur with MAPbI3 perovskite include hydration reaction and decomposition reaction. The specific reactions are as follows:

[0043] 4MAPbI3+4H2O→4[MAPbI3·H2O]

[0044] MA4PbI6→2H2O+3PbI2+2H2O

[0045] The reaction products of the above reaction are grey and yellow.

[0046] It should be noted that there is not only one way to distribute the perovskite crystallization detection reagent on the surface of the material to be tested. It can be dripping, dipping, or coating. As long as the perovskite crystallization detection reagent can be distributed on the surface of the material to be tested, technicians in this field can choose according to actual conditions.

[0047] In this embodiment, the material to be tested is immersed in the perovskite crystallization detection reagent for 10 seconds, and the material to be tested is placed on a water platform and allowed to stand at room temperature of 25°C until the volatile components in the perovskite crystallization detection reagent are completely volatilized, and the morphology of the material to be tested is observed, and the detection conclusion is drawn based on the morphology of the material to be tested.

[0048] After the volatile components in the perovskite crystal detection reagent volatilize, the color presented by the material to be tested includes one or more of black, brown, gray, yellow, red, and white; in this embodiment, the color presented by the material to be tested is mainly black, brown, gray, and yellow. If the color grayscale of the material to be tested is high, the perovskite crystal quality is high; if the color grayscale of the material to be tested is low, the perovskite crystal quality is low.

[0049] In this embodiment, the color of the material to be tested is originally black. After the perovskite crystal detection reagent is used and the volatile components therein volatilize, the color changes, which indicates that the perovskite is partially destroyed. The different degrees of color change represent the quality of the perovskite crystallization, and the darker the color, the better the crystallization quality. Therefore, the quality of the perovskite crystallization can be judged by observing the morphology of the material to be tested, that is, the color and color distribution.

[0050] like Figure 1 , which is a front view of the material to be tested before testing; Figure 2 The back view of the material to be tested before testing is shown; Figure 3 This is a front view of the material to be tested obtained after testing using the perovskite crystallization detection reagent of Example 1; Figure 4 This is a back view of the material to be tested obtained after testing using the perovskite crystal detection reagent of Example 1. Figure 1-2 It can be seen that the surroundings of the material to be tested and the active area on the back are all black. There are obvious gray-white gaps on the back, indicating that there are regional differences in the crystallization of perovskite. Figure 3-4It can be seen that the originally black area on the front of the material to be tested has partially turned yellow, brown or gray. The color change indicates that the perovskite has been partially destroyed. The different degrees of color change represent the quality of the reaction crystallization. The darker the color, the better the crystallization quality. From the back, the color change can also be found; and the original gap has almost completely disappeared, indicating that the perovskite has fully reacted with the etching solution, resulting in reconstruction.

[0051] As an optional implementation of this embodiment, the quality of the perovskite crystal can also be judged by the color distribution of the material to be tested. If the area of ​​the region with high grayscale of the material to be tested is large, the perovskite crystal quality is high; if the area of ​​the region with low grayscale of the material to be tested is large, the perovskite crystal quality is low.

[0052] As an alternative implementation, the solar cell may also be any one of a formal mesoporous structure perovskite solar cell, a formal planar structure perovskite solar cell, a trans-mesoporous structure perovskite solar cell, and a trans-planar structure perovskite solar cell.

[0053] Example 2

[0054] The perovskite crystallization detection reagent of this embodiment includes: an active substance and an anti-solvent;

[0055] The active substance is hydrogen peroxide, the anti-solvent is isopropanol, and the perovskite crystal detection reagent is prepared by mixing hydrogen peroxide and isopropanol in a volume ratio of 1:9.

[0056] The perovskite crystal detection method of this embodiment includes the following steps:

[0057] Taking a material to be tested, distributing the perovskite crystallization detection reagent on the surface of the material to be tested, and volatilizing the volatile components of the perovskite crystallization detection reagent, determining the morphology of the material to be tested, and obtaining a detection conclusion;

[0058] Wherein, the material to be tested is an electrode of a solar cell having a perovskite crystal structure. In this embodiment, the solar cell is a printable mesoscopic MAPbI3 perovskite solar cell.

[0059] The active substance is a weak oxidant H2O2, which mainly undergoes the following iodine ion oxidation reaction with MAPbI3:

[0060] 2I - +H2O2+2H + →I2+2H2O

[0061] The reaction product of the above reaction is red.

[0062] In this embodiment, the method of distributing the perovskite crystallization detection reagent on the surface of the material to be tested is as follows: the perovskite crystallization detection reagent is dripped onto the surface of the material to be tested, the material to be tested is placed on a water platform, and allowed to stand at room temperature of 25°C until the volatile components in the perovskite crystallization detection reagent are completely volatilized, the morphology of the material to be tested is observed, and the detection conclusion is drawn based on the morphology of the material to be tested.

[0063] After the volatile components in the perovskite crystal detection reagent volatilize, the color presented by the material to be tested includes one or more of black, brown, gray, yellow, red, and white; in this embodiment, the color presented by the material to be tested is mainly black, brown, gray, and red. If the color grayscale of the material to be tested is high, the perovskite crystal quality is high; if the color grayscale of the material to be tested is low, the perovskite crystal quality is low.

[0064] In this embodiment, the color of the material to be tested is originally black. After the perovskite crystal detection reagent is used and the volatile components therein volatilize, the color changes, which indicates that the perovskite is partially destroyed. The different degrees of color change represent the quality of the perovskite crystallization, and the darker the color, the better the crystallization quality. Therefore, the quality of the perovskite crystallization can be judged by observing the morphology of the material to be tested, that is, the color and color distribution.

[0065] As an optional implementation of this embodiment, the quality of the perovskite crystal can also be judged by the color distribution of the material to be tested. If the area of ​​the region with high grayscale of the material to be tested is large, the perovskite crystal quality is high; if the area of ​​the region with low grayscale of the material to be tested is large, the perovskite crystal quality is low.

[0066] As an alternative implementation, the solar cell may also be any one of a formal mesoporous structure perovskite solar cell, a formal planar structure perovskite solar cell, a trans-mesoporous structure perovskite solar cell, and a trans-planar structure perovskite solar cell.

[0067] Example 3

[0068] The perovskite crystallization detection reagent of this embodiment includes: an active substance and an anti-solvent;

[0069] The active substance is 4-tert-butylpyridine, the anti-solvent is isopropanol, and the perovskite crystal detection reagent is an isopropanol solution of 4-tert-butylpyridine with a molar concentration of 0.05 mol / L.

[0070] The perovskite crystal detection method of this embodiment includes the following steps:

[0071] Taking a material to be tested, distributing the perovskite crystallization detection reagent on the surface of the material to be tested, and volatilizing the volatile components of the perovskite crystallization detection reagent, determining the morphology of the material to be tested, and obtaining a detection conclusion;

[0072] Wherein, the material to be tested is an electrode of a solar cell having a perovskite crystal structure. In this embodiment, the solar cell is a printable mesoscopic MAPbI3 perovskite solar cell.

[0073] The active substance is 4-tert-butylpyridine (t-BP), which reacts with MAPbI3 mainly as follows:

[0074] MAPbI3+t-BP→MAI+PbI2·t-BP

[0075] The reaction product of the above reaction, PbI2·t-BP, is an adduct of lead iodide and t-BP, and is yellow or white.

[0076] In this embodiment, the method of distributing the perovskite crystallization detection reagent on the surface of the material to be tested is as follows: the perovskite crystallization detection reagent is coated on the surface of the material to be tested, the material to be tested is placed on a water platform, and allowed to stand at room temperature of 25°C until the volatile components in the perovskite crystallization detection reagent are completely volatilized, the morphology of the material to be tested is observed, and the detection conclusion is drawn based on the morphology of the material to be tested.

[0077] After the volatile components in the perovskite crystal detection reagent volatilize, the color presented by the material to be tested includes one or more of black, brown, gray, yellow, red, and white; in this embodiment, the color presented by the material to be tested is mainly black, brown, gray, yellow, and white. If the color grayscale of the material to be tested is high, the perovskite crystal quality is high; if the color grayscale of the material to be tested is low, the perovskite crystal quality is low.

[0078] In this embodiment, the color of the material to be tested is originally black. After the perovskite crystal detection reagent is used and the volatile components therein volatilize, the color changes, which indicates that the perovskite is partially destroyed. The different degrees of color change represent the quality of the perovskite crystallization, and the darker the color, the better the crystallization quality. Therefore, the quality of the perovskite crystallization can be judged by observing the morphology of the material to be tested, that is, the color and color distribution.

[0079] As an optional implementation of this embodiment, the quality of the perovskite crystal can also be judged by the color distribution of the material to be tested. If the area of ​​the region with high grayscale of the material to be tested is large, the perovskite crystal quality is high; if the area of ​​the region with low grayscale of the material to be tested is large, the perovskite crystal quality is low.

[0080] As an alternative implementation, the solar cell may also be any one of a formal mesoporous structure perovskite solar cell, a formal planar structure perovskite solar cell, a trans-mesoporous structure perovskite solar cell, and a trans-planar structure perovskite solar cell.

[0081] Example 4

[0082] The perovskite crystallization detection reagent of this embodiment includes: an active substance and an anti-solvent;

[0083] Wherein, the active substance is formic acid, the anti-solvent is isopropanol, and the perovskite crystal detection reagent is an isopropanol solution of formic acid with a molar concentration of 0.05 mol / L.

[0084] The perovskite crystal detection method of this embodiment includes the following steps:

[0085] Taking a material to be tested, distributing the perovskite crystallization detection reagent on the surface of the material to be tested, and volatilizing the volatile components of the perovskite crystallization detection reagent, determining the morphology of the material to be tested, and obtaining a detection conclusion;

[0086] Wherein, the material to be tested is an electrode of a solar cell having a perovskite crystal structure. In this embodiment, the solar cell is a printable mesoscopic MAPbI perovskite solar cell.

[0087] The active substance is formic acid, which mainly reacts with MAPbI3 as follows:

[0088] MAPbI3+HCOOH→MAI-HCOOH+PbI2

[0089] Wherein, MAI-HCOOH represents the hydrogen bonding interaction between MAI and formic acid; the reaction product of the above reaction is yellow.

[0090] In this embodiment, the method of distributing the perovskite crystallization detection reagent on the surface of the material to be tested is as follows: immersing the material to be tested in the perovskite crystallization detection reagent for 10 seconds, placing the material to be tested on a water platform, and standing at room temperature of 25°C until the volatile components in the perovskite crystallization detection reagent are completely volatilized, observing the morphology of the material to be tested, and drawing the detection conclusion based on the morphology of the material to be tested.

[0091] After the volatile components in the perovskite crystal detection reagent volatilize, the color presented by the material to be tested includes one or more of black, brown, gray, yellow, red, and white; in this embodiment, the color presented by the material to be tested is mainly black, brown, gray, and yellow. If the color grayscale of the material to be tested is high, the perovskite crystal quality is high; if the color grayscale of the material to be tested is low, the perovskite crystal quality is low.

[0092] In this embodiment, the color of the material to be tested is originally black. After the perovskite crystal detection reagent is used and the volatile components therein volatilize, the color changes, which indicates that the perovskite is partially destroyed. The different degrees of color change represent the quality of the perovskite crystallization, and the darker the color, the better the crystallization quality. Therefore, the quality of the perovskite crystallization can be judged by observing the morphology of the material to be tested, that is, the color and color distribution.

[0093] As an optional implementation of this embodiment, the quality of the perovskite crystal can also be judged by the color distribution of the material to be tested. If the area of ​​the region with high grayscale of the material to be tested is large, the perovskite crystal quality is high; if the area of ​​the region with low grayscale of the material to be tested is large, the perovskite crystal quality is low.

[0094] As an alternative implementation, the solar cell may also be any one of a formal mesoporous structure perovskite solar cell, a formal planar structure perovskite solar cell, a trans-mesoporous structure perovskite solar cell, and a trans-planar structure perovskite solar cell.

[0095] Example 5

[0096] The perovskite crystallization detection reagent of this embodiment is exactly the same as the perovskite crystallization detection reagent in Example 1, with the only difference being that the volume fraction of the active substance is greater than 10%.

[0097] Effect comparison ratio

[0098] In order to verify the technical effect of the perovskite crystallization detection reagent of the present invention, the following experiments were conducted:

[0099] Step 1: Take 5 electrodes of printable mesoscopic perovskite solar cells of equal size as initial cells, and test the initial photoelectric conversion efficiency according to the method of complete active area test; then, take pictures of the 5 electrodes under equal conditions, calculate the grayscale average of the pictures, and obtain the initial grayscale average; wherein the grayscale value ranges from 0 to 255, white is 255, and black is 0. The grayscale average refers to the average value calculated by calculating the grayscale value in the picture according to the area weight.

[0100] Step 2: Use the electrodes of the 5 initial batteries in step 1 as the materials to be tested, take the perovskite crystallization detection reagent in Examples 1-5, and detect the perovskite crystallization quality of the materials to be tested respectively according to the corresponding perovskite crystallization detection method, take pictures of the tested materials under the same conditions, calculate the grayscale average of the pictures, and obtain the first grayscale average; and test the photoelectric conversion efficiency according to the complete active area test method to obtain the first photoelectric conversion efficiency.

[0101] Step three: Use the electrodes of the five batteries in step two as the materials to be tested, take the perovskite crystallization detection reagent in Examples 1-5 again, and detect the perovskite crystallization quality of the materials to be tested respectively according to the corresponding perovskite crystallization detection method, take pictures of the tested materials under the same conditions, calculate the grayscale average of the pictures, and obtain the second grayscale average; and test the photoelectric conversion efficiency according to the complete active area test method to obtain the second photoelectric conversion efficiency.

[0102] After experimentation, the results are as follows:

[0103]

[0104] It can be seen from the above results that the perovskite crystallization detection reagent of the present invention can judge the quality of perovskite crystallization, especially in Example 2, the degree of damage to the material to be tested changes minimally with the increase in the number of tests, and a more stable test result can be obtained.

[0105] It is known from common technical knowledge that the present invention can be implemented by other embodiments that do not deviate from its spirit or essential features. Therefore, the above disclosed embodiments are only illustrative in all respects and are not exclusive. All changes within the scope of the present invention or within the scope equivalent to the present invention are included in the present invention.

Claims

1. A method for detecting perovskite crystallization, characterized in that: The steps include: Taking a material to be tested, distributing a perovskite crystallization detection reagent on the surface of the material to be tested, and volatilizing the volatile components of the perovskite crystallization detection reagent, determining the morphology of the material to be tested, and obtaining a detection conclusion; Wherein, the material to be tested is an electrode of a solar cell having a perovskite crystal structure; Wherein, the perovskite crystallization detection reagent is prepared by mixing water and isopropanol in a volume ratio of 1:9; or, The perovskite crystal detection reagent is prepared by mixing 4-tert-butylpyridine and isopropanol, and the molar concentration of the 4-tert-butylpyridine is 0.05 mol / L; or, The perovskite crystallization detection reagent is prepared by mixing hydrogen peroxide and isopropanol in a volume ratio of 1:9; Wherein, the perovskite crystallization detection reagent is distributed on the surface of the material to be tested by dripping; or, the perovskite crystallization detection reagent is distributed on the surface of the material to be tested by immersion; or, the perovskite crystallization detection reagent is distributed on the surface of the material to be tested by coating; The test conclusion is obtained based on the morphology of the material to be tested: The colors of the material to be tested include black, brown, gray, yellow, red, and white; if the grayscale of the color of the material to be tested is high, the perovskite crystal quality is high; if the grayscale of the color of the material to be tested is low, the perovskite crystal quality is low.

2. The perovskite crystal detection method according to claim 1, characterized in that: If the area of ​​the material to be tested with high grayscale is large, the perovskite crystal quality is high; if the area of ​​the material to be tested with low grayscale is large, the perovskite crystal quality is low.

3. The perovskite crystal detection method according to claim 1, characterized in that: The solar cell is one of a printable mesoscopic perovskite solar cell, a formal mesoporous structure perovskite solar cell, a formal planar structure perovskite solar cell, an inverted mesoporous structure perovskite solar cell, and an inverted planar structure perovskite solar cell.

Citation Information

Patent Citations

  • Composite photocatalyst for producing hydrogen peroxide as well as preparation method and application thereof

    CN111203257A